Experimental human-computer interaction : a practical guide with visiual examples - Purchase, Helen C. (Cambridge University Press, 2012)
"Experiments that require the use of human participants are time consuming and costly: it is important to get the process right the first time. Planning and preparation are key to success. This practical book takes the human-computer interaction researcher through the complete experimental process, from identifying a research question to designing and conducting an experiment, and then to analyzing and reporting the results. The advice offered in this book draws on the author's twenty years of experience running experiments. In describing general concepts of experimental design and analysis she refers to numerous worked examples that address the very real practicalities and problems of conducting an experiment, such as managing participants, getting ethical approval, preempting criticism, choosing a statistical method, and dealing with unexpected events"-- Provided by publisher